Analyzing the Expression Profile of AREB/ABF and DREB/CBF Genes under Drought and Salinity Stresses in Grape (Vitis vinifera L.). - Hana Zandkarimi (PLoS ONE, 2015)
Expression patterns of four candidate AREB/ABF genes and four DREB/CBF genes were evaluated in leaf and root tissues of five grape varieties ('Qalati', 'Kaj Angoor', 'Sabz Angoor', 'Siahe Zarghan', 'Bidane Safid') with differential response to drought stress. Among the AREB/ABF genes, AREB1 and ABF2 showed up-regulation in response to drought stress in leaf and root tissues of all varieties while AREB2 and ABF1 showed down-regulation in both leaf and root tissues of the sensitive variety 'Bidane Sefid' in response to drought and salt stress. Among the DREB/CBF genes, CBF4 was the most responsive to drought stress in both leaf and root tissues. CBF2 and CBF3 showed up-regulation in all varieties in response to drought stress in leaf except in 'Bidane Sefid'. Under salinity stress, AREB2 and ABF2 showed up-regulation in response to the increasing level of salinity in the leaf tissues but in the root tissues ABF2 was up-regulated in response to increasing NaCl concentration while AREB2 was down-regulated. Therefore, it seems AREB2 has tissue-specific response to salinity stress. All CBF genes were up-regulated in response to salinity stress in the leaf and root tissues. Expression data suggested that CBF2 is more responsive to NaCl stress. Among all four promising and stress tolerant varieties 'Siah Zarghan' and 'Kaj Angoor' were more tolerant than 'Qalati' and 'Sabz Angoor' to drought and salinity.